2020
DOI: 10.1111/cas.14276
|View full text |Cite
|
Sign up to set email alerts
|

CD155 contributes to the mesenchymal phenotype of triple‐negative breast cancer

Abstract: Patients with triple‐negative breast cancer (TNBC) lack molecular targets and have an unfavorable outcome. CD155 is overexpressed in human cancers, but whether it plays a role in TNBC is unexplored. Here we found that CD155 was enriched in both TNBC cell lines and tumor tissues. High CD155 expression was related to poor prognosis of breast cancer patients. CD155 was associated with a mesenchymal phenotype. CD155 knockdown induced a mesenchymal‐epithelial transition in TNBC cells, and suppressed TNBC cell migra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(16 citation statements)
references
References 57 publications
3
13
0
Order By: Relevance
“…Our observation of a more rounded, less mesenchymal morphology in CD155-depleted cells has been described previously in glioma cells 14 , and studies in triple-negative aggressive breast cancer cells demonstrated CD155 contribution to the mesenchymal cell state 63 . Depletion of CD155 in these cells triggered mesenchymal to epithelial transition and repressed migration and invasion in vitro and in vivo., suggesting that CD155 expression in MB cells could also contribute to migration control indirectly via transcriptional reprogramming.…”
Section: Discussionsupporting
confidence: 86%
“…Our observation of a more rounded, less mesenchymal morphology in CD155-depleted cells has been described previously in glioma cells 14 , and studies in triple-negative aggressive breast cancer cells demonstrated CD155 contribution to the mesenchymal cell state 63 . Depletion of CD155 in these cells triggered mesenchymal to epithelial transition and repressed migration and invasion in vitro and in vivo., suggesting that CD155 expression in MB cells could also contribute to migration control indirectly via transcriptional reprogramming.…”
Section: Discussionsupporting
confidence: 86%
“…CD155 functions as a multi‐functional molecule in human cancers 24 . Previous studies reported that CD155 promoted cell proliferation through Ras‐Raf‐MEK‐ERK signaling pathway 25 and contributed to mesenchymal phenotype in breast cancer 26 . In addition, CD155 overexpression could induce tumor immune escape via interacting with co‐inhibitory receptors on T cells and NK cells 12,27 .…”
Section: Discussionmentioning
confidence: 99%
“…Collectively, these changes, when they are accompanied by the expression of specific transcription factors and molecular modifications [ 40 ] are referred to as tumor cell epithelial-mesenchymal transition (EMT) [ 41 , 42 ]. Indeed, the causal relationship between ICPML expression on tumor cells and EMT has been shown in several instances with a variety of technical approaches (e.g., siRNA, CRISPR/Cas) [ 43 , 44 , 45 , 46 , 47 ]. Expression of ICPMLs on tumor cells can be both a consequence [ 48 ], as well as a cause of tumor cell EMT [ 43 , 44 , 49 , 50 , 51 ], suggesting the existence of a positive feedback loop between the expression of ICPMLs and EMT [ 9 ].…”
Section: The Consequences Of the Expression Of Icpmls On The Biology Of Tumor Cellsmentioning
confidence: 99%
“…Indeed, the causal relationship between ICPML expression on tumor cells and EMT has been shown in several instances with a variety of technical approaches (e.g., siRNA, CRISPR/Cas) [ 43 , 44 , 45 , 46 , 47 ]. Expression of ICPMLs on tumor cells can be both a consequence [ 48 ], as well as a cause of tumor cell EMT [ 43 , 44 , 49 , 50 , 51 ], suggesting the existence of a positive feedback loop between the expression of ICPMLs and EMT [ 9 ]. Interestingly, tumor cell EMT can also have immunosuppressive effects [ 52 ] and it has recently been shown that loss of the epithelial marker E-cadherin, a hallmark of EMT, reduces responsiveness to ICIs in a mouse melanoma model [ 53 ].…”
Section: The Consequences Of the Expression Of Icpmls On The Biology Of Tumor Cellsmentioning
confidence: 99%
See 1 more Smart Citation